What to do with literary manuscripts? A model for manuscript studies after 1700. Issue 1 (November 2018) - Van Mierlo, Wim
Abstract : In 1967, the French scholar Louis Hay published an opinion piece in Le Monde under the title "Des manuscrits, pour quoi faire?" Hay's piece came at the start of a critical practice, called "critique génétique", which proposed to study not the product, but the process of literary creation by returning to the manuscripts and drafts in which this process is recorded. Thus it gave meaning to the notion of the modern manuscript. Genetic criticism has since developed into a small but robust field of literary studies within and outside of France. But despite sharing an object in common, genetic criticism as a text-oriented approach has surprisingly little basis in archival practices and concepts. Reviewing some of the obvious differences between genetic criticism and archive studies, this article aims to bring the two areas closer together. It proposes a holistic approach to the study of literary manuscripts that takes into account composition history and the growth of the text, the physical and material nature of the documents and the culture in which the manuscript was produced. The latter two entail a call for, on the one hand, the development of a "modern palaeography" capable of analysing the intricate complexities of modern drafts, handwriting and writing tools and, on the other, a consideration of a manuscript culture that elucidates common writing practices and uses of manuscripts across the last three centuries.